Long‐term administration of pyridostigmine attenuates pressure overload‐induced cardiac hypertrophy by inhibiting calcineurin signalling. Issue 9 (10th March 2017) - Lu, Yi; Zhao, Ming; Liu, Jin‐Jun; He, Xi; Yu, Xiao‐Jiang; Liu, Long‐Zhu; Sun, Lei; Chen, Li‐Na; Zang, Wei‐Jin
Abstract: Cardiac hypertrophy is associated with autonomic imbalance, characterized by enhanced sympathetic activity and withdrawal of parasympathetic control. Increased parasympathetic function improves ventricular performance. However, whether pyridostigmine, a reversible acetylcholinesterase inhibitor, can offset cardiac hypertrophy induced by pressure overload remains unclear. Hence, this study aimed to determine whether pyridostigmine can ameliorate pressure overload‐induced cardiac hypertrophy and identify the underlying mechanisms. Rats were subjected to either sham or constriction of abdominal aorta surgery and treated with or without pyridostigmine for 8 weeks. Vagal activity and cardiac function were determined using PowerLab. Cardiac hypertrophy was evaluated using various histological stains. Protein markers for cardiac hypertrophy were quantitated by Western blot and immunoprecipitation. Pressure overload resulted in a marked reduction in vagal discharge and a profound increase in cardiac hypertrophy index and cardiac dysfunction. Pyridostigmine increased the acetylcholine levels by inhibiting acetylcholinesterase in rats with pressure overload. Pyridostigmine significantly attenuated cardiac hypertrophy based on reduction in left ventricular weight/body weight, suppression of the levels of atrial natriuretic peptide, brain natriuretic peptide and β‐myosin heavy chain, and a reduction in cardiac fibrosis. These effects were accompanied by marked improvement of cardiac function. Additionally, pyridostigmine inhibited the CaN/NFAT3/GATA4 pathway and suppressed Orai1/STIM1 complex formation. In conclusion, pressure overload resulted in cardiac hypertrophy, cardiac dysfunction and a significant reduction in vagal discharge. Pyridostigmine attenuated cardiac hypertrophy and improved cardiac function, which was related to improved cholinergic transmission efficiency (decreased acetylcholinesterase and increased acetylcholine), inhibition of the CaN/NFAT3/GATA4 pathway and suppression of the interaction of Orai1/STIM1.